2002
DOI: 10.1074/jbc.m207705200
|View full text |Cite
|
Sign up to set email alerts
|

Low Density Lipoprotein (LDL) Receptor-related Protein 1B Impairs Urokinase Receptor Regeneration on the Cell Surface and Inhibits Cell Migration

Abstract: The low density lipoprotein (LDL) receptor-related protein 1B (LRP1B) is a newly identified member of the LDL receptor family and is closely related to LRP. It was discovered as a putative tumor suppressor and is frequently inactivated in lung cancer cells. In the present study, we used an LRP1B minireceptor (mLRP1B4), which mimics the function and trafficking of LRP1B, to explore the roles of LRP1B on the plasminogen activation system. We found that mLRP1B4 and urokinase plasminogen activator receptor (uPAR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
53
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 33 publications
8
53
0
Order By: Relevance
“…Although located adjacent to a fragile site, FRA2F is the least sensitive fragile site in the aphidicolin fragility assay and scored highest in a computational measure for homozygous deletion selection pressure (54). In vitro data also supports a role for LRP1B as a tumor suppressor with LRP1B interacting with uPAR to inhibit cell migration (61). Overexpression of LRP1B inhibits cell growth and colony formation in vitro and tumor formation in nude mice (45).…”
Section: Discussionmentioning
confidence: 64%
“…Although located adjacent to a fragile site, FRA2F is the least sensitive fragile site in the aphidicolin fragility assay and scored highest in a computational measure for homozygous deletion selection pressure (54). In vitro data also supports a role for LRP1B as a tumor suppressor with LRP1B interacting with uPAR to inhibit cell migration (61). Overexpression of LRP1B inhibits cell growth and colony formation in vitro and tumor formation in nude mice (45).…”
Section: Discussionmentioning
confidence: 64%
“…Aside from modulating matrix metalloproteinase 2, as shown here, LRP1B has also been reported to regulate the uPA system (Liu et al, 2001). Cells expressing LRP1B display a substantially slower rate of uPA/plasminogen activator inhibitor type-1 complex internalization (Knisely et al, 2007), which impairs the regeneration of unoccupied urokinase plasminogen activator receptor on the cell surface and correlates with a diminished rate of cell migration (Li et al, 2002;Tanaga et al, 2004). Our results highlight LRP1B as an unconventional and yet key tumor suppressor acting as a regulator of the 'extracellular proteome' and constraining the abundance of critical members of proteolytic systems in the tumor microenvironment.…”
Section: Lrp1b Inactivation Modulates the Extracellular Microenvironmentmentioning
confidence: 98%
“…Previous studies have shown that LRP-1 function directly affects expression of uPA, PAI-1, and uPAR (39). In this study, LRP-1-expressing MeT5A PMCs and LRP-1-deficient REN were used in internalization assays.…”
Section: Discussionmentioning
confidence: 99%